Respiration as exercise limiting factor - Boutellier, U.
Limitation of maximal exercise is generally explained by cardiovascular or neuromuscular factors. In healthy subjects, the respiratory system is not considered to be an exercise limiting factor. In highly trained athletes oxygen diffusion limitations may occur but the respiratory pump should have enough reserve because even sedentary subjects are able to increase their breathing enough during heavy exercise. In daily life and during many athletic events, the ability to sustain a given percentage of VO2max for a period of time (endurance) is more relevant than VO2max itself. During this constant-load exercise the respiratory system can become a limiting factor: Different studies have shown that diaphragmatic fatigue may develop. We found that an isolated endurance training of the respiratory muscles (isocapnic hyperpnea, 3-5 x 30min per week for 4-6 weeks) significantly increased the time to exhaustion at an exercise level between 64 and 85% VO2max. This prolongation of exercise duration was up to 50% in sedentary and 30% in physically active subjects. The respiratory training also significantly increased respiratory endurance and maximal voluntary ventilation but it did not affect the anaerobic threshold nor VO2max. In contrast to physical endurance training, respiratory muscle training did not increase cardiac stroke volume. Also the decrease in blood lactate concentration during exercise after respiratory training, when compared to pre-training, can not explain the prolongation of cycling performance after respiratory training. We speculate that the increase in exercise endurance is related to a reduced development of respiratory muscle fatigue after respiratory endurance training. Towards the end of heavy exercise at a constant workload, minute ventilation typically increases (due to overproportionally increased breathing frequency) and subjects become short of breath. This rapid, sometimes shallow, breathing has been shown to occur when respiratory muscles are fatigued. After respiratory training, this ventilatory increase is frequently reduced, supporting the hypothesis of a reduced development of respiratory muscle fatigue after respiratory training. In addition to healthy persons, also patients will benefit from our research. Dr. W. Bauer at the Lindenhofspital, Bern, could show that respiratory training significantly reduces snoring at night. Dr. T. Scherer (Lungenzentrum Hirslanden) showed that subjects suffering from chronic obstructive pulmonary disease increase their respiratory and walking performance and feel better during normal daytime activities after respiratory endurance training. Also, findings in chronically hyperventilating patients (S. Jack and Dr. C.J. Warburton, Aintree Hospital, Liverpool) suggest that respiratory training may reduce their symptoms and normalize their breathing at rest and during exercise. In summary, respiratory endurance training alone can prolong exercise time during constant-load exercise in both sedentary and active subjects and it can improve symptoms in respiratory patients. These observations suggests that the role of respiratory muscles during endurance exercise has been underestimated so far.